2010
DOI: 10.5093/tr2010v26n3a8
|View full text |Cite
|
Sign up to set email alerts
|

Satisfacción Laboral y Burnout en Trabajos Poco Cualificados: Diferencias entre Sexos en Población Inmigrante

Abstract: Resumen. El objetivo de este estudio es profundizar en el análisis de la satisfacción laboral en trabajos de escasa cualificación realizados por personas inmigrantes, buscando posibles diferencias entre hombres y mujeres. Se analiza una muestra de 250 inmigrantes en España procedentes de diferentes culturas. Las variables evaluadas son: satisfacción laboral, burnout y diferentes características laborales. No se han encontrado diferencias entre hombres y mujeres respecto al burnout ni a la satisfacción laboral.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…In Portugal there are mixed findings, with some studies not finding statistically significant differences among men and women [133,134] while others reported that men had higher job satisfaction than women [135]. Past studies in other countries found differences between sexes both with males having greater job satisfaction after controlling for similar job ranks [136], or the reverse effect [137], or even the absence of differences between women and men [138,139]. Kaiser [135] found that job satisfaction differences among sexes are expected to be insignificant within a higher job status segment.…”
Section: Discussionmentioning
confidence: 99%
“…In Portugal there are mixed findings, with some studies not finding statistically significant differences among men and women [133,134] while others reported that men had higher job satisfaction than women [135]. Past studies in other countries found differences between sexes both with males having greater job satisfaction after controlling for similar job ranks [136], or the reverse effect [137], or even the absence of differences between women and men [138,139]. Kaiser [135] found that job satisfaction differences among sexes are expected to be insignificant within a higher job status segment.…”
Section: Discussionmentioning
confidence: 99%
“…Conviene destacar que, dentro de la satisfacción laboral existen factores extrínsecos, del entorno de trabajo e intrínsecos que reflejan las experiencias de los individuos con el mismo. La satisfacción intrínseca aborda aspectos como el reconocimiento obtenido por el trabajo, la responsabilidad y aspectos relativos al contenido de sus funciones (Moreno et al, 2010). Por otro lado, la satisfacción extrínseca proviene de factores como la satisfacción con el salario, las políticas de la empresa, las oportunidades de promoción o la estabilidad en el trabajo (Cruz et al, 2011).…”
Section: La Satisfacción Laboralunclassified